2009
DOI: 10.1007/s00359-009-0484-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual detection of diminutive floral guides in the bumblebee Bombus terrestris and in the honeybee Apis mellifera

Abstract: Many flowers display colour patterns comprising a large peripheral colour area that serves to attract flower visitors from some distance, and a small central, contrastingly coloured area made up by stamens or floral guides. In this study, we scaled down the size of floral guides to detect the minimal size bumblebees (Bombus terrestris) and honeybees (Apis mellifera) require for guidance. We analyzed the approach and the precise contact of the antennal tips with the floral guide of artificial flowers which prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…1). Both visual elements are visible to bumble bees, which can discriminate a floral nectar guide that is ≥0.5 mm in diameter at close distances, such as when they walk on the flower (Lunau et al 2009). On the disjunct feeders, the nectary was displaced 37 mm away, to the opposite side of the feeder (Fig.…”
Section: Nectar Guidementioning
confidence: 99%
See 1 more Smart Citation
“…1). Both visual elements are visible to bumble bees, which can discriminate a floral nectar guide that is ≥0.5 mm in diameter at close distances, such as when they walk on the flower (Lunau et al 2009). On the disjunct feeders, the nectary was displaced 37 mm away, to the opposite side of the feeder (Fig.…”
Section: Nectar Guidementioning
confidence: 99%
“…Bumble bees can approach and discriminate artificial flowers with circular nectar guides at least 2 mm in diameter over artificial flowers without nectar guides (Lunau et al 2009). However, as they approach a flower, bumble bees can detect even smaller nectar guides and will antennate artificial flowers with circular nectar guides as small as 0.5 mm (Lunau et al 2009). Leonard et al (2013) used a white artificial flower with a central dark nectary that was 2.5 mm in diameter.…”
Section: Visibility Of Nectar Guide and Nectarymentioning
confidence: 99%
“…This particular form of nectar guide has long been known to increase floral attractiveness to a range of pollinators. Bumblebees and honeybees have been shown to discriminate bull's eye spots as little as 2mm in diameter (Lunau et al 2009). In a series of classic experiments with Delphinium nelsonii, which has a white centre in a deep blue flower, Waser and Price (1983;1985) showed that the central colour patch improves foraging efficiency of both bees and hummingbirds by reducing time to find the flower and time to access the reward.…”
Section: Introductionmentioning
confidence: 99%
“…2 cm; Goulson et al, 2007); entering a corridor, in which a pattern is contained, in a maze (Simonds and Plowright, 2004;Séguin and Plowright, 2008); antennal contact with a test pattern (Pohl et al, 2008;Lunau et al, 2009)-see Fig. 1 for an illustration with honeybees and bumblebees; landing on a test pattern (Leonard and Papaj, 2011); floral exploration as defined by walking into an artificial flower (Orbán and Plowright, 2013); or probing (Daumer, 1958).…”
Section: Measures Of Preferencementioning
confidence: 99%
“…Flowers with a dot or pair of dots at the centre of flower (Fig. 1) are more likely to be approached and antennated by flower-naïve bumblebees (Heuschen et al, 2005), with bigger dots eliciting stronger responses by both honeybees and bumblebees (Lunau et al, 2009). …”
Section: Floral Guidesmentioning
confidence: 99%